Chronic kidney disease and risk for cardiovascular and limb outcomes in patients with symptomatic peripheral artery disease: The EUCLID trial. (October 2019) - Hopley, Charles W; Kavanagh, Sarah; Patel, Manesh R; Ostrom, Cara; Baumgartner, Iris; Berger, Jeffrey S; Blomster, Juuso I; Fowkes, F Gerry R; Jones, W Schuyler; Katona, Brian G; Mahaffey, Kenneth W; Norgren, Lars; et al.
In patients with symptomatic peripheral artery disease (PAD), the impact of chronic kidney disease (CKD) on major adverse cardiovascular events has not been fully evaluated. The Examining Use of Ticagrelor In PAD (EUCLID) trial randomized 13, 885 patients with PAD to ticagrelor 90 mg twice daily or clopidogrel 75 mg daily. This post hoc analysis compared the incidence of the primary composite endpoint (cardiovascular death, myocardial infarction (MI), or ischemic stroke) in patients with CKD (eGFR < 60 mL/min/1.73 m 2 ) with those without CKD (eGFR ⩾ 60 mL/min/1.73 m 2 ). The primary safety endpoint was thrombolysis in MI (TIMI) major bleeding. A total of 13, 483 patients were included; 3332 (25%) had CKD, of whom 237 had stage 4/5 disease. Median follow-up was approximately 30 months. After statistical adjustment, patients with CKD had a higher rate of the primary endpoint compared with those without CKD (6.75 vs 3.72 events/100 patient-years; adjusted hazard ratio (HR) 1.45, 95% CI 1.30–1.63). CKD was not associated with increased risk of hospitalization for acute limb ischemia (ALI) (adjusted HR 0.96, 95% CI 0.69–1.34) or major amputation (adjusted HR 0.92, 95% CI 0.66–1.28). CKD was not associated with a significantly increased risk of major bleeding (adjusted HR 1.21, 95% CI 0.89–1.64), but minor bleeding was significantly increased (adjusted HR 1.51, 95% CI 1.07–2.15). In conclusion, patients with PAD and CKD had higher rates of cardiovascular death, MI, and ischemic stroke, but similar rates of ALI, major amputation, and TIMI major bleeding when compared with patients without CKD.ClinicalTrials.gov Identifier: NCT01732822